Impact Behavior of FRP-Strengthened RC Beams without Stirrups - Pham, T.; Hao, Hong (American Society of Civil Engineers, 2016)
This study investigates the impact behavior of fiber-reinforced polymer (FRP)-strengthened reinforced concrete (RC) beams and FRP contribution to shear strength. Thirteen RC beams (1,500×150×250 mm) were tested against static and impact loads. The beams were strengthened with FRP U-wraps and 45°-angle wraps to investigate the effectiveness of different wrapping schemes. The experimental results show that the debonding strain of FRP under impact loads is slightly smaller than that under static loads. The FRP contribution to shear strength is discussed and verified against a design code. In terms of using the same amount of FRP, 45°-angle FRP wraps provide better performance than the FRP U-wraps in terms of both the load capacity and displacement. Fully wrapping a RC beam with FRP is more efficient than wrapping distributed FRP strips. The impact behavior and failure modes of FRP strengthened RC beams are also discussed.